Media Coverage and Immigration Worries: Econometric Evidence - Christine Benesch; Simon Loretz; David Stadelmann; Tobias Thomas (Center for Research in Economics, Management and the Arts (CREMA), 2018)
This paper empirically explores the link between mass media coverage of migration and immigration worries. Using detailed data on media coverage in Germany, we show that the amount of media reports regarding migration issues is positively associated with concerns about immigration among the German population. The association is robust to the inclusion of time-variant individual control variables and individual fixed-effects. We employ media spillovers from the neighboring country of Switzerland, which occur due to referendum decisions on immigration as an instrumental variable to address endogeneity concerns. The IV estimates suggest that media coverage has a causal impact on immigration worries. Exploring heterogeneous effects between respondents, the results reveal that the link between media reports and immigration worries is particularly relevant for women and respondents active in the workforce.
Keywords: L8; D7; F2; 330; media; migration; news spillovers; political attitudes